[Haskell-cafe] Would you mind explain such a code ?
z_axis at 163.com
Thu Sep 10 02:20:30 EDT 2009
myFoldl :: (a -> b -> a) -> a -> [b] -> a
myFoldl f z xs = foldr step id xs z
where step x g a = g (f a x)
I know myFoldl implements foldl using foldr. However i really donot know how
it can do it ?
Please shed a light one me, thanks!
View this message in context: http://www.nabble.com/Would-you-mind-explain-such-a-code---tp25377949p25377949.html
Sent from the Haskell - Haskell-Cafe mailing list archive at Nabble.com.
More information about the Haskell-Cafe